Studies 15 / Innovation in Greek Manufacturing - Kazis D. A; Skoumal S; Centre Of Planning And Economic Research (1985)
Role of Advanced Technologies and New Management Outlook. Summary, Introduction, Greek Manufacturing, Advanced Technology Sectors, Conditions for Technological Advancement, Product Proposals, Needed Measures, The Product Development Authority, Summary of Conclusions and Recommendations, Appendices, Bibliography, List of Tables and Figures.